ENVIRONMENTAL AND GENETIC FACTORS ON GROWTH TRAITS OF BLACK BONI SHEEP IN YEMEN - ABED AL-BIAL; JAI SINGH; D. P. SINGH; RAM NIWAS (The Bioscan, 2012)
The data were collected from 1992 to 2009 of Black Boni sheep maintained at the Regional Research Station in the Central Highlands of Yemen. Data were analyzed to study the effects of environmental and genetic factors on body weight and growth rate from birth to weaning. The overall least-square means for body weights were 2.18 kg, 10.58 kg 98.68 g for birth, weaning and growth rate respectively. Year of birth effects were significant (p< 0.05) on BW, WW and growth rate. Also, analysis of variance showed that the sex of the lambs and type of birth were important sources of variation (p<0.05) for all traits. The size of the ewe during lambing had also significant effect (p< 0.01) on birth. The results show direct heritability for all traits was 0.38 of BW, 0.30 of WW and 0.26 of growth rate. Higher estimates of heritability for growth performance traits refers to of presence of more additive genetic variance.